PENGARUH KEMAMPUAN KERJA, DISIPLIN KERJA DAN PELATIHAN KERJA TERHADAP PRESTASI KERJA BERDASARKAN PERSEPSIKARYAWAN PT. KARYA PATRA ABADI BALIKPAPAN - Suhartono, Suhartono; Fauzan, Muhammad Oceano; Amelia, Risky (Sekolah Tinggi Ilmu Ekonomi Balikpapan, 2022)
This study aims to determine the effect of work ability, work discipline and job training on job performance based on employee perceptions PT. Karya Patra Abadi Balikpapan. The location of this research was conducted at JL. Lt. Gen. Soeprapto no. 69 Balikpapan, East Kalimantan. The population is 114 people and the sample used in this study is 89 respondents. The analysis technique used is multiple linear regression analysis. The results of the regression analysis, obtained that (X1) workability partially has a positive and significant effect on employee work performance. Variable (X2)work discipline partially positive and significant effect. The variable (X3) partially positive and significant job training. And together (simultaneously) work ability, work discipline and job training have a positive and significant effect on employee performance.